Answer:a
Step-by-step explanation:
Answer:
A) x greater than or equal to −3
Step-by-step explanation:
We have the following inequality:
7 − 9x − (x + 12) ≤ 25
Solving the inequation, we have:
7 − 9x − x - 12 ≤ 25
-10x ≤ 30
-x ≤ 3
x≥-3
Therefore the result is option A) x greater than or equal to −3
Answer:
f'(x) = (x + 1)/15
Step-by-step explanation:
f(x) = 15x -1,
Think of the term "f(x)" as a single variable, then solve for the term "x", manipulate the equation like how one would manipulate a literal equation, by inverse operations.
f(x) = 15x - 1
+1 +1
f(x) + 1 = 15x
/15 /15
(f(x) + 1)/15 = x
This means that (denote in the way one would denote an inverse of a function);
f'(x) = (x + 1)/15
Answer:
102
Step-by-step explanation:
78 and x are adjacent angles.
Sum of adjacent angles is 180 in a parallelogram.
78 + x = 180
x = 180 - 78
x = 102
Answer:1928
Step-by-step explanation:488* 6
I used lattice